MUSIC, DANCE AND MESSAGING IN THE GHANAIAN POLITICAL ARENA - Jebuni, T. S.; Bukari, G. A. (UDS International Journal of Development, 2025)
This paper examines how music and dance shape electoral accountability in Ghanaian politics. With political party proliferation and the electoral contestation in Africa in the 1990s, scholars began to explore factors that influence electoral outcomes. Numerous academic studies have found a number of characteristics that impact electoral outcomes in the new democracies, including clientelism, ethnicity, retrospective voting, ideological stances, and rational voting. Beyond these factors, music and dance play an important role in the multiparty electoral systems in Ghana. Despite this purpose, there is comparatively little research on how dance and music contribute to electoral responsibility. Our paper contributes to filling this knowledge gap by analyzing music and dance in the Ghanaian electoral politics by analyzing the impact of â€˜Yen tie Obiaa,â€™campaign song for the 2016 and 2020 general elections by a Ghanaian Highlife icon, Charles Kwadwo Fosu (a.k.a Daddy Lumba). Drawing from twenty (20) participants, the findings revealed that lyrics of the song in addition to other electoral undercurrents have also adversely affected the candidature of the National Democratic Congress (NDC), and influenced voters who hitherto had no intention of voting for the New Patriotic Party candidate in the 2016 and 2020 presidential election. Â Keywords: Popular Music and Dance, Messaging, Ghanaian political arena, Democracy, Elections, Multi-party